Quality of soybean seeds after inoculation of biologicals in the field (Research, Society and Development, 2021)
The combination of nitrogen-fixing bacteria and biocontrolling fungi that interfere with the development of plants can be a tool to promote a better quality of seeds obtained under these combinations. The objective of this work was to verify the interaction of bioproducts based on Bradyrhizobium japonicum, Azospirillum brasilense, Trichoderma asperrellum and BioAx applied to the soil to improve seed quality in soybean cultivars. The experimental design used was completely randomized in a 3 × 4 factorial scheme, with three replications. The treatments consisted of three soybean cultivars [Brasmax Foco IPRO, Brasmax Desafio IPRO and Brasmax Bonus IPRO] and four biological [T1- Azospirillum brasilense + Bradyrhizobium japonicum, T2- BioAx, T3- Trichoderma asperrellum, and T4- the combination of the three biologicals]. It was evaluated: the first germination count, germination, electrical conductivity, dry mass of the area and seedling roots and tetrazolium test (vigor and viability). The results showed that the responses obtained were dependent on the cultivars evaluated, and that Brasmax Foco IPRO and Brasmax Desafio IPRO showed higher physiological seed quality. The effect of biologicals depends on the soybean cultivar; in cultivars with higher physiological quality, the biological effect is not evident. However, in cultivars with a lower physiological quality (Brasmax Bonus IPRO), the effect of biologicals is more evident, thus constituting an excellent alternative to improve the quality of soybean seeds with the combined use of biologicals.